DEVELOPMENT OF MODELS FOR THE DECISION-MAKING PROCESS REGARDING THE CHOICE OF URBAN PASSENGER VEHICLES - Burenko, Volodymyr; Guseva-Bozhatkina, Viktoriia (SWorld-Ger Conference proceedings, 2025)
The work considers the process of selecting vehicles for delivery to full stops of urban passenger transport. Conceptual hierarchical models of benefits and costs were built for decision-making. The development of a multi-criteria mathematical model with